The use of equipment and multimedia systems in the english language teaching-learning process, in private primary schools, inCuenca - Guerrero Vázquez, Maritza Fabiola
I have divided this thesis into four main chapters. The first chapter, ?WHAT IS MULTIMEDIA?, where we talk about the multimedia systems importance in the teaching-learning process. Why should teachers use multimedia for teaching? Talking books where children can see the text and pictures. They can click on the loudspeaker icon to hear the texts spoken. Second, ?PRINCIPAL EQUIPMENT AND MULTIMEDIA SYSTEMS THAT AN EDUCATIONAL INSTITUTION SHOULD HAVE FOR TEACHING FOREIGN LANGUAGES? here we considered eleven principal equipment and Multimedia systems that an educational institution should have for teaching foreign languages, such as: Personal and laptop computers, CD players, speakers, microphone-hearing aids, webcams, printers, scanners, television, projectors, DVDs, sound equipment and digital cameras. Third, ?PROS AND CONS OF USING MULTIMEDIA SYSTEMS IN THE LANGUAGE CLASSROOM?, here we consider why teachers need to use multimedia instruments in order to have better results in the teaching learning process. We involve the roles of Multiple Intelligences in the Creation of Multimedia projects; and the importance of the role of Information and Communication Technologies in education (ICT). Fourth, ?APPLICATION AND EXCERSICES?, Power Point is a tool used for presenting information in a dynamic slide. Teaching language classes using computer programs such as word and excel. Using the internet in order to prepare classes is another important thing that teachers need to know in order to be prepared into this Multimedia society. In this chapter we include games, activities and ideas about how to use multimedia systems in the language class